2005
DOI: 10.1111/j.1744-7348.2005.040031.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of species‐specific primers for the ectoparasitic nematode species Xiphinema brevicolle, X. diffusum, X. elongatum, X. ifacolum and X. longicaudatum (Nematoda: Longidoridae) based on ribosomal DNA sequences

Abstract: The objective of this study was to develop single-step PCR species-specifi c primers that reliably discriminate four economically important Xiphinema species (X. brevicolle, X. elongatum, X. ifacolum and X. longicaudatum) and X. diffusum that is taxonomically very similar to X. brevicolle. Each species-specifi c reverse primer was located in the ITS-1 rDNA region and was used in combination with a universal forward primer located in the 18S rDNA gene. Primer reliability was confi rmed by screening seven and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The morphometrics of the Hungarian isolate are in agreement with the original description of the species, but when compared with the topotypes (Luc et al, 1998), this Hungarian isolate has a longer body (2.1 vs 1.9 mm); and higher 'c' values (82 vs 77), shorter odontostyle (94 vs. 101 µm), a more anterior position of guiding ring (79 vs 86µm); and vulva (V=49.5 vs 53%). To resolve this contradiction, molecular methods (Lazarova et al, 2006;Oliveira et al, 2005) will have to be involved in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometrics of the Hungarian isolate are in agreement with the original description of the species, but when compared with the topotypes (Luc et al, 1998), this Hungarian isolate has a longer body (2.1 vs 1.9 mm); and higher 'c' values (82 vs 77), shorter odontostyle (94 vs. 101 µm), a more anterior position of guiding ring (79 vs 86µm); and vulva (V=49.5 vs 53%). To resolve this contradiction, molecular methods (Lazarova et al, 2006;Oliveira et al, 2005) will have to be involved in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The application of molecular techniques to supplement taxonomic and systematics studies on the genus Xiphinema particularly in the X. americanum group has revealed that within the X. americanum-group some longassumed single species are in fact cryptic (i.e. genetically distinct but morphologically almost indistinguishable) (Barsi & De Luca 2008;Oliveira et al 2005Oliveira et al , 2006Archidona-Yuste et al 2016a;Lazarova et al 2016). Unfortunately, only a small number of Portuguese populations of this taxonomic group have been molecularly characterized (He et al 2005;Molinari et al 1997Molinari et al , 2006Lazarova et al 2006) and, as a result, the taxonomic status of some species of the X. americanum-group reported in Portugal has been contentious.…”
Section: Family Longidoridae In Portugalmentioning
confidence: 99%
“…Morphometrics of J3 are similar to type population except ratio 'a' which is smaller (38.9, 37.1 vs 50) than the type population. It has been demonstrated that for routine identification of plant parasitic nematodes, DNA based diagnostics are quicker than the traditional strategy using morphology and morphometrics (Wang et al, 2003;Oliveira et al, 2005), but morphological identification is still a prerequisite for DNA based diagnostics. Therefore, in this research note detailed morphometrics of X. dentatum are provided from the Czech Republic.…”
Section: Resultsmentioning
confidence: 99%